MATHEMATICAL MODELING AS A LENS OF THE REAL WORLD - Prus, Alla (Physical and Mathematical Education, 2023)
Formulation of the problem.Mathematical modeling today is not just a trend, but an urgent need for education. However, the introduction of this method into the school course of Mathematics as a method of scientific research and the basis for the development, for acquiring mathematical knowledge and skills is quite limited.Materials and Methods. The analysis of the courseware on the research problem; the systematization and generalization of different approaches to determine the content of mathematical modelling; the analysis and systematization of domestic and foreign experience in using the method of mathematical modelling.Results. A part of our research on the content of mathematical modelling in education abroad (based on publications in English-language sources) and in Ukraine in this paper is presented. Various definition statements of mathematical modelling are considered, the terms that scientists use when studying this concept are outlined. The attention is focused on the importance of the analysis of mathematical modelling as an activity and the structure as well. The cycle schemes of mathematical modelling, which are most often used in the scientific and methodological papers, are introduced. Based on the analysis of the structures of the competence in mathematical modelling that are described in the studies of various authors groups of subcompetences have been identified. They are important for the formation of skills to solve the corresponding model problems.Conclusions. Disclosing the content of the mathematical modelling concept will help the teacher focus on the specific individual actions that students should master in order to successfully complete the entire cycle of mathematical modelling. The condition of strong interest of teachers of Mathematics and the availability of relevant knowledge and skills in the actual use of mathematical modelling in the school course of Mathematics and in the corresponding University courses are important.
Keywords: modelling; applied problem; practical problem; model problem; the cycle of mathematical modelling; the competencies of the mathematical modelling